(untitled) (Hematology Meeting Reports, 2009)
atients with von Willebrand disease that do not respond to desmopressin should be treated with von Willebrand factor (VWF) concentrates in connection with bleedings and surgery. A recent in vitro investigation of six VWF concentrates showed large differences in composition, VWF activity and relative content of VWF and FVIII. Furthermore, different viral inactivation methods had been used. The VWF:RCo/VWF:Ag ratio ranged from 0.15-0.91, which illustrates the large differences in inactivation of VWF. This ratio correlated well with the relative amount of the high molecular weight multimers of the VWF (HMWH) in concentrates, which ranged between 15-100% of that in normal plasma. Concentrates lacking the HMWM may be less effective for mucosal bleeds. FVIII is more important for surgical hemostasis. In this study the FVIII/VWF:RCo ratios varied considerably between 0.02-6. Concentrates with a high VWF/FVIII ratio may induce very high levels of FVIII in patients, as endogenously released FVIII adds to the infused FVIII. The concentrate that was almost devoid of FVIII should be given 12-24 hours before surgery in order to allow the endogenously released FVIII to increase sufficiently, or be combined with a FVIII concentrate. It is important to be aware of the differences between the concentrates as it may have significant clinical implications.